he Contribution of E-Satisfaction and E-Word of Mouth in Influencing E- Loyalty on E-Commerce Platforms in Indonesia: The Mediating Role of Cybersecurity - bertha napitupulu; Francisca Hermawan; Widarto Rachbiniwidarto@univpancasila (UNIB Press, 2026)
This study aims to examine the relationship betweenelectronic customer satisfaction (e-Satisfaction), electronicWord of Mouth (e-WOM), and cybersecurity as a mediatingvariable, in shaping electronic customer loyalty (e-Loyalty)on e-commerce platforms in Indonesia. This study employs adescriptive quantitative approach, with data collected througha questionnaire distributed via Google Forms, involving 652active users of e-commerce platforms such as Tokopedia,Shopee, and Bukalapak.The results of the analysis using SmartPLS show thate-Satisfaction and e-WOM have a positive and significanteffect on e-Loyalty. However, cybersecurity has nosignificant direct effect and does not significantly mediate therelationship between e-Satisfaction and e-WOM on e-Loyalty. The novelty of this study lies in its investigation ofthe mediating role of cybersecurity within the context ofIndonesian e-commerce consumer loyalty behavior—anaspect that has not been extensively explored empirically.The practical implications of this study emphasize theimportance of e-commerce platforms prioritizingimprovements in customer satisfaction as a primary strategyfor building loyalty, while cybersecurity should neverthelessbe maintained as a foundation of consumer trust. This studyprovides strategic insight for developing a sustainable userexperience within Indonesia's digital infrastructure